Osmotic Fragility Status of Red Blood Cell In Patients With Chronic Kidney Disease - Khatun, Monira; Chowdhury, Mohammed Nasim Uddin; Hossain, Kamal; Khanam, Shamima; Ahmed, Farhena; Rownak, Nihad (Journal of Chittagong Medical College Teachers' Association, 2017)
Background: Anaemia is an almost invariable consequence of Chronic Kidney Disease. Among other causes, excessive haemolysis is also seen in advanced renal failure. The aim of this study is to observe the range of osmotic fragility of RBC in patients with chronic kidney disease and correlate the fragile states of RBC with different stages of chronic kidney disease. Materials and methods: It is a hospital based cross sectional observational study. 100 patients of diagnosed case of chronic kidney disease admitted in the Department of Nephrology, Chittagong Medical College Hospital were selected as cases and 100 apparently healthy persons, age and sex matched were selected as controls. Osmotic fragility of RBC was determined manually by traditional method in the department of Physiology, Chittagong Medical College, Chittagong. Data were analyzed by different statistical methods. Results: In our study, among the case group (100 patients), we found that 5.5% were on CKD stage III, 21% on stage IV, 23.5% on stage V. And 50% (100 apparently healthy subjects) were taken as control. Among the case group RBC osmotic fragility was decreased in 69% and remaining 31% was normal. Here the mean (±SD) of strength of NaCl solution were 0.30 (±0.05) and 0.44(±0.04)% in case and control group respectively where RBCs were partially hemolysed. The mean (±SD) of strength of NaCl Solution were 0.11 (±0.10) and 0.21(±0.09)% in case and control group respectively where RBCs were completely hemolysed. Again the mean (±SD) of strength of NaCl Solution were 0.33 (±0.03), 0.29 (±0.06) and 0.30(±0.05)% in CKD patients with stage III, IV and V respectively where RBCs were partially hemolysed. The mean (±SD) of strength of NaCl soluton were 0.14 (±0.09) and 0.08(±0.10)% and 0.12(±0.10)% in CKD patients with stage III, IV and V respectively where RBCs were completely hemolysed. Conclusion: The results of this study revealed that osmotic fragility status of RBC of CKD patients was significantly decreased which were inconsistent with other study. JCMCTA 2017 ; 28 (1) : 52 - 56